Answer:
First option: 4
Explanation:
We know that "j" varies directly with "m" and inversely with "p". Then, it is a Combined variation with the following form:
![j=k((m)/(p))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jijissm9jo954a7rh0j05g6it4141pdtjf.png)
Where "k" is the constant of variation.
Then, in order to find "k", we need to substitute the given values of "j", "m" and "p" into the equation and solve for "k":
![32=k((2)/((1)/(4)))\\\\32=8k\\\\k=(32)/(8)\\\\k=4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cklq497u1fkpf0f5t5vzle7mlf2ygg6qy2.png)